Snodgrass Procedure (TIP), game changing procedure: A single Surgeon’s Experience - Rahman, Md Samidur; Reza, Md Shahin; Tanjida, Zinat; Leema, Elora Afroz; Sonet, Nazmul Haider Chowdhury; Abir, Md Ashekin; Datta, Prosenjit (Journal of Paediatric Surgeons of Bangladesh, 2025)
Background: Hypospadias is the most common congenital anomaly of male urogenital tract. Different aspects of hypospadias such as its etiology, classification and treatment have been a place of discussion. More than 300 methods have been tried for correction of hypospadias. No single technique has been accepted as gold standard because of diversity of results of different methods and different outcome. The of surgical technique depends on the surgeon’s personal experience and training. Aim: The aim of our study is to see the outcome of Snodgrass procedure in distal hypospadias as well of proximal hypospadias where the urethral plate is adequate and having minimal chordee. Methods: This is a retrospective study conducted in a single unit of Dept. of Pediatric Surgery DMCH and a private hypospadias center by a single surgeon where total 96 patients out of 152 were operated by Snodgrass (TIP) procedure from July 2022 to September 2023. Data were analyzed and results were compared with other recently published studies. Results: Out of 96 patients, 7 patients developed single UC fistula among which 3 healed spontaneously and 3 needed repair after 6 months. 5 patients developed meatal stenosis who required regular dilation with the help of the tip of a feeding tube lubricated with 2% jesocaine jelly and low potential steroid ointment. 2 patients developed partial glans disruption and 4 patients lost epidermal layer of skin, all of which healed spontaneously without residual scar. Conclusion: The TIP or Snodgrass technique is the most popular option for distal hypospadias and proximal hypospadias without severe chordee and having good outcomes. Journal of Paediatric Surgeons of Bangladesh (2020) Vol. 11 (1 & 2):11-16